1999
DOI: 10.1046/j.1365-2141.1999.01507.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obstetric factors on cord blood donation for transplantation

Abstract: Summary. Recent reports have shown that low nucleated cell dose signi®cantly decreases survival after cord blood transplantation. Prior to starting clinical cord blood banking we investigated the impact of obstetric factors on cell dose and volume of cord blood donations. Cord blood was obtained from 114 normal full-term deliveries. Mean volume collected was 93´5 ml, mean total nucleated cell count (TNC) was 13´1´10 8 . Statistical analysis was by backwards stepwise regression. Signi®cant factors affecting nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
80
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 15 publications
(18 reference statements)
7
80
1
Order By: Relevance
“…However, the multiple linear regression analyses in the present study show the significantly positive correlations between the total LD/CD34 + cells and maternal/neonatal factors (Table 3). These results are consistent with most of the previous reports (Donaldson et al 1999;Yamada et al 2000;Li et al 2001;George et al 2006;Mancinelli et al 2006), including that meconium in the amniotic fluid correlates with better cell counts (Askari et al 2005). Therefore the total LD cells per CB unit analyzed in the present study can be assumed as a substitute variable instead of the total nucleated cells in some previous studies (Lasky et al 2002;Mohyeddin Bonab et al 2004;Solves et al 2005), and can be also confirmed by other previous studies (Pafumi et al 2001;Bornstein et al 2005).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, the multiple linear regression analyses in the present study show the significantly positive correlations between the total LD/CD34 + cells and maternal/neonatal factors (Table 3). These results are consistent with most of the previous reports (Donaldson et al 1999;Yamada et al 2000;Li et al 2001;George et al 2006;Mancinelli et al 2006), including that meconium in the amniotic fluid correlates with better cell counts (Askari et al 2005). Therefore the total LD cells per CB unit analyzed in the present study can be assumed as a substitute variable instead of the total nucleated cells in some previous studies (Lasky et al 2002;Mohyeddin Bonab et al 2004;Solves et al 2005), and can be also confirmed by other previous studies (Pafumi et al 2001;Bornstein et al 2005).…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with several previous studies showing that maternal age does not affect either nucleated cells or CD34 + cells (Donaldson et al 1999;Nakagawa et al 2004;George et al 2006;Mancinelli et al 2006). However, focusing on the 1-gravidae alone, the maternal age of 1-gravidae have a slightly positive correlation with the total LD cells (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations